Contribution to the hazard assessment of benchmark metallic nanomaterials through a set of in vitro genotoxicity assays - Vital, Nádia (2019)
Background and Aim: Metall-based nanomaterials (NMs) are among the most commonly applied manufactured nanomaterials (NM). Regardless of the considerable efforts to assess their safety, the presently available data do not allow for general and consistent conclusions. Moreover, the validity of the classical in vitro testing systems for NMs hazard assessment has been questioned and needs confirmation. The present study aimed at evaluating the toxicity of three benchmark metallic NMs - titanium dioxide (NM-100),cerium dioxide (NM-212) and nanosilver - with different physicochemical properties, using a battery of in vitro genotoxicity assays, in an attempt to characterize their toxicity profile.